Karakteristik Organoleptik Daging Itik Cihateup yang Diberi Ransum Mengandung Ampas Teh Hijau Fermentasi dan Probiotik Lactobacillus sp - Lutfi Ginayah; Nurul Frasiska; Andri Kusmayadi (LPPM Perjuangan University of Tasikmalaya, 2023)
Green tea dregs fermentation process is carried out to reduce crude fiber and tannins, as well as increase nutritional value and digestibility in livestock. Probiotic Lactobacillus sp combined with fermented green tea dregs is thought to optimize metabolic processes in the digestive tract. The urgency of this research is to utilize green tea dregs that has been fermented and combined with the probiotic Lactobacillus sp. as a feed additive for Cihateup ducks. This study aims to determine the effect of giving a combination of green tea dregs and probiotic Lactobacillus sp in rations on the organoleptic quality of duck meat. This study used a completely randomized design with 4 treatments and 5 replications. The treatment in this study was the addition of fermented green tea dregs (ATHF) and probiotic Lactobacillus sp with different levels, namely P1 (100% basal feed/PB + 0% ATHF), P2 (96% PB + 1% ATHF + 3% Probiotics) , P3 (96% PB + 2% ATHF + 2% Probiotics), and P4 (96% PB + 3% ATHF + 1% Probiotics). The results of this study showed that the addition of fermented green tea dregs and probiotic Lactobacillus sp to this ration had no significant effect (P>0.05) on the organoleptic characteristics (taste, color, aroma, texture) of duck meat.